Intervention of Apartment Developers in the Management of Apartments in Indonesia - Andrian, Andrian (Journal La Sociale, 2025)
The existence of flat is a solution to fulfill the housing needs of citizens considering the limited land to build landed house. Each flat consists of common property, common share, and common land. The management of the flats is carried out by owner corporation, either by forming their own building management or by appointing an external building management. The current problem is the intervention by developer in the management of flats that occurred in several flats in Indonesia. In fact, there several cases regarding the formation of owner corporation that should be facilitated by developers, but have not been carried out consistently and optimally by developers. The intervention by developer in flat management will have potential for privatization and management monopoly, which will be detrimental to flat’s owner. Therefore, the local government and the department of housing should supervise developer’s performance and ensure that developers are aware of and carry out their obligations under the law. To examine this problem, I apply normative juridical methods with qualitative analysis techniques. I also use several approaches in conducting the analysis, such as case approach, conceptual approach, and statute approach.